Analisis Strategi Pengembangan Kompetensi Pegawai Pada Badan Kepegawaian Dan Pegembangan Sumber Daya Manusia Kabupaten Nias Utara - Agus Ratna Mawarni Harefa; Syah Abadi Mendrofa; Yamolala Zega; Sukaaro Waruwu (Visi Sosial Humaniora, 2024)
Developing employee competency is crucial in improving the quality of public services. In the era of globalization and increasingly fierce competition, local governments are required to have superior human resources and be able to adapt quickly to change. Therefore, employee competency development strategies are very important to ensure the achievement of organizational goals in providing excellent service to the community. The variables in this research consist of 1 (one) single variable, namely: A single variable is a variable that only has one dimension or category. This variable only has one value or attribute for each unit of analysis. According to Sugiyono (2017: 39), research variables are "all attributes, traits, values of people who have certain variations determined by researchers to be studied and then drawn conclusions". The following is an analysis of research results obtained from observations and in-depth interviews regarding employee competency development at the Personnel and Development Agency. North Nias Regency Human Resources. This research was carried out carefully, paying attention to the location and time that had been optimally arranged. Apart from that, researchers also met directly with informants to obtain more accurate data. The results of this research were obtained through data collection techniques in the form of interviews and observations. This technique was chosen to obtain natural data. The interview structure designed by the researcher is not standard, so that if the answers given by the informant are not clear, the researcher will ask additional questions to deepen and clarify the information provided by the informant. This research aims to analyze employee competency development strategies at the North Nias Regency Personnel and Human Resources Development Agency (BKPSDM). The research results show that: BKPSDM has implemented various competency development strategies, such as training, formal education, and job rotation. However, there are still several obstacles that need to be overcome, such as budget limitations, lack of employee interest, and a less than optimal evaluation system. Therefore, it is necessary to improve and refine existing competency development strategies, as well as develop new strategies that are more effective and efficient. The factors that influence the successful implementation of the employee competency development strategy at BKPSDM North Nias Regency have been implemented well, so that employees experience an increase in their ability to carry out their duties.